Comparative Steady State Analysis of Boost and Cascaded Boost Converter with Inductive ESR losses & Capacitor Current Behaviour - Tanmoy Roy Choudhury; Byamakesh Nayak (Institute of Advanced Engineering and Science, 2016)
In this paper, an overall comparison between the Boost Converter (BC) & Cascaded Converter/ Cascaded Boost Converter (CBC) has been depicted in terms of ideal condition, as well as with the consideration of Equivalent Series Resistance (ESR) of inductor(s). The loss comparison in the two converters due to the ESR is also included in this paper. It can be seen that in CBC, voltage gain is more but the power loss due to ESR is also more compared to BC. The parameters of the converters are derived with a consideration of per unit ripple quantity of inductor current and capacitor voltage. A boundary condition between the continuous conduction mode (CCM) & discontinuous conduction mode (DCM) of the inductor current is also shown. The behaviour of the capacitor current for the converters is discussed during ON and OFF condition of the switch(es) during DCM. At the end, the simulation results of both the converters are given for a 20V/100V, 100 W output. The analysis and simulation results are presented in this paper for the verification of the feasibility.